2019
DOI: 10.1002/ese3.341
|View full text |Cite
|
Sign up to set email alerts
|

Predictive control based on occupant behavior prediction for domestic hot water system using data mining algorithm

Abstract: Domestic hot water systems are a primary source of energy consumption in buildings, and present a promising future in terms of energy saving. Predictive control methods have been used to reduce energy consumption during an operation period. However, current methods lack consideration of occupant behavior, which significantly influences the prediction results. In this study, a data‐based predictive method is proposed to predict the shower behavior of occupants. A dataset was collected from seven occupants and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Support Vector Machines (SVM) are useful for prediction problems because they can handle both linear and non-linear data [160]. SVMs are also less prone to overfitting and produce solid results even with small sample sizes [24,26,139,161,164]. Notwithstanding, the performance is largely dependent on a suitable kernel and parameter adjustment, which can be a difficult undertaking.…”
Section: Machine Learning Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Support Vector Machines (SVM) are useful for prediction problems because they can handle both linear and non-linear data [160]. SVMs are also less prone to overfitting and produce solid results even with small sample sizes [24,26,139,161,164]. Notwithstanding, the performance is largely dependent on a suitable kernel and parameter adjustment, which can be a difficult undertaking.…”
Section: Machine Learning Methodsmentioning
confidence: 99%
“…✓ Shan et al [42] ✓ ✓ K. Ahmed et al [1] ✓ ✓ George et al [36] ✓ ✓ ✓ Edwards et al [52] ✓ ✓ ✓ ✓ ✓ K. Ahmed et al [4] ✓ ✓ Chmielewska et al [53] ✓ ✓ de Santiago et al [26] ✓ Ferrantelli et al [43] ✓ ✓ ✓ Fuentes et al [2] ✓ ✓ ✓ ✓ Marszal et al [6] ✓ ✓ ✓ Rouleau et al [37] ✓ ✓ ✓ Ivanko et al [5] ✓ ✓ ✓ De Simone et al [29] ✓ ✓ ✓ ✓ ✓ ✓ Xie and Noor [54] ✓ ✓ ✓ ✓ Tolofari et al [55] ✓ ✓ ✓ Mostafaeipour et al [56] ✓ ✓ ✓ ✓ Meireles et al [57] ✓ C. Chen et al [58] ✓ ✓ ✓ ✓ Alipour et al [59] ✓ ✓ ✓ Sarabia-Escriva et al [28] ✓ ✓ ✓ a Influencing factor considered by authors.…”
Section: Rathnayaka Et Al [40]mentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed model predicts the cumulative hot water usage for the next day by taking into account of recent trends of historical data. Cao et al [101] used SVM to predict the shower behavior of occupants to forecast the hot water usage. The authors collected data from seven occupants and the results showed that, compared to a traditional control method, the proposal can reduce heat loss by up to 33%.…”
Section: Supervised Machine Learningmentioning
confidence: 99%
“…Data mining has emerged as an alternative tool for modeling and forecasting due to its ability to capture the non-linearity in the data. While the shortcoming of data mining is a large amount of training data [14], with the advent of big data era, data mining has recently been widely used for demand forecasting in the various fields, where data can be collected easily, such as energy [10,15], tourism [16,17], transportation [18][19][20], water management [21,22], remanufacturing [23], bike sharing [24,25], retail pharmacies [26], hospitals [27,28], logistics [14], and spare parts management [14,[29][30][31], showing its usefulness.…”
Section: Reviews On Related Workmentioning
confidence: 99%